Making sense of maritime supply chain: A relationship marketing approach - Oluyomi Abayomi Osobajo; Ioannis Koliousis; Heather McLaughlin (Journal of Shipping and Trade (JST), 2021)
Building a relationship with the maritime supply chain partners is considered imperative for organisations to survive and remain competitive. Yet, several studies that examined the maritime supply chain have not adequately explored nor assessed the relationship constructs that impacts maritime supply chain performance. This study intends to fill this gap and ascertain the influence that certain relationship elements have on the maritime supply chain performance. The study is solely a desk research. After providing a general overview of maritime supply chain and its structure, relationship marketing paradigm and relationship constructs, this study examines the influence that the identified relationship constructs (i.e. trust, commitment and satisfaction) has on supply chain performance. The study asserts that the present of the identified relationship constructs (i.e. trust, commitment and satisfaction) among supply chain partners will influence supply chain performance positively. Hence, building a successful long-term relationship among maritime supply chain partners requires an understanding of these key relationship constructs.
Keywords: 650; Maritime; Relationship; Relationship marketing; Relationship quality; Supply chain; Supply chain management